State Loss as the Basis for Criminalizing Corruption by State-Owned Enterprise Employees - Harry Harmono; Ade Adhari (Jurnal Daulat Hukum, 2026)
This study aimed to examine the legal certainty of the sentencing basis in the cassation ruling of Supreme Court Decision Number 283 K/Pid.Sus/2021, and to formulate the ideal sentencing model for determining the legal basis for imposing sanctions on corruption committed by State-Owned Enterprise (BUMN) employees. The research method used was normative legal research with a statutory approach and case approach, analyzing court decisions through library research and qualitative-prescriptive analysis. The novelty in this research lies in the identification of a structural normative weakness in the Supreme Court's reasoning, where the choice of article was based on the magnitude of state losses rather than systematic proof of the elements of the offense a practice that creates legal uncertainty and potential double standards in law enforcement. Based on the research, it was concluded that the cassation decision contained argumentation weaknesses from the standpoint of Gustav Radbruch's theory of legal certainty, and the ideal sentencing model must build juridical qualification in a structured manner, concretely prove formal unlawfulness, and integrate the principle of proportionality combining retributive, preventive, and restorative dimensions in a balanced manner.